Leveraging Consumer Behavior Research for Effective Marketing Strategies - Kumo, Wardani (Advances in Business & Industrial Marketing Research, 2023)
Purpose: This study aims to explore how consumer behavior research can be leveraged to develop effective marketing strategies. The focus is on understanding the factors influencing consumer choices and how these insights can inform targeted marketing approaches. Research Design and Methodology: The research employs a qualitative literature review methodology, systematically collecting and analyzing scholarly articles, books, and reports from various academic databases. The study synthesizes insights to provide a comprehensive understanding of consumer behavior dynamics and their implications for marketing strategy. Findings and Discussion: The findings highlight that consumer behavior is influenced by a combination of demographic, psychographic, cultural, situational, and technological factors. Understanding these factors allows marketers to tailor their strategies to specific consumer segments. The study also emphasizes the importance of digital technologies in shaping consumer behavior, presenting both opportunities and challenges for marketers. Effective marketing strategies must address consumer privacy concerns and leverage emerging technologies such as AI and VR to enhance consumer engagement. Implications: The study underscores the necessity for marketers to integrate consumer behavior insights into their strategic planning. By adopting a multi-perspective approach and embracing technological advancements, marketers can create personalized and impactful marketing campaigns. Future research should focus on sustainability, interdisciplinary collaborations, and continuous exploration of emerging trends to stay aligned with evolving consumer preferences.